Perceived health-related quality of life and selected characteristics of inpatients with rheumatic diseases - Koudeláková, Ludmila; Kalánková, Dominika; Bartoníčková, Daniela; Škopík, Dominik; Kisvetrová, Helena (Central European Journal of Nursing and Midwifery, 2024)
Aim: To assess the perceived health-related quality of life (HRQoL) in hospitalized patients with rheumatic diseases and to determine whether selected characteristics can affect their perceived quality of life. Design: A cross-sectional study. Methods: Data were collected between September 2022 and March 2023 using the standardized instrument to measure HRQoL, namely the RAND 36-Item Health Survey (SF-36). The sample consisted of 170 patients with rheumatic diseases hospitalized in a teaching hospital in the Czech Republic. Results: The average perceived HRQoL was 34.94 (SD = 17.06), indicating poor quality of life. The most highly rated subscale was 'emotional well-being' (56.02 ± 15.71), and the lowest rated subscale was 'role limitations due to physical health' (11.76 ± 28.54). The HRQoL subscales were significantly correlated with Mini-Mental State Examination (MMSE) score, self-care activities, pain severity, age of the patients, and length of hospitalization. Differences in HRQoL were identified based on education, social status, use of compensatory aids, attendance at social events, and history of falls in the past year (p < 0.05). Conclusion: The study contributes to the existing body of knowledge on the subject, but also underscores the importance of considering holistic factors when evaluating HRQoL in individuals with rheumatic diseases.
Keywords: Holistic Nursing; holistické ošetřovatelství; kvalita života; lidé; kvalita zdravotní péče; Rheumatic Diseases; Quality of Life; Česká republika; průřezové studie; Quality of Health Care; Cross-Sectional Studies; Czech Republic; Hospitalization; Humans; revmatické nemoci; hospitalizace